2006
DOI: 10.1097/01.brs.0000240271.39583.b6
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Exposure of the Spine for Removal of Lumbar Interbody Devices and Implants

Abstract: Anterior removal of lumbar interbody devices placed anteriorly or posteriorly has a high incidence of complication. Average blood loss and hospital stay are increased with revision anterior surgery. The vascular complication rate is 2-fold higher at L4-L5 level compared to L5-S1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 7 publications
0
36
0
2
Order By: Relevance
“…As in the three cases in our series, vascular injuries can occur during the surgical approach to the spine [13], but they can also happen while the discectomy (or implant removal) is being performed [5]. They are more frequent at L4-L5 than at L5-S1, because of the position of the iliac bifurcation and tethering of the iliolumbar vein [3,5,13]. In an attempt to avoid vascular injury and limit SD standard deviation blood loss during spine exposure, it is essential to obtain control of the vessels proximally and/or distally at previously nonoperated levels before mobilization of the vasculature and exposure of the target intervertebral level [13].…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…As in the three cases in our series, vascular injuries can occur during the surgical approach to the spine [13], but they can also happen while the discectomy (or implant removal) is being performed [5]. They are more frequent at L4-L5 than at L5-S1, because of the position of the iliac bifurcation and tethering of the iliolumbar vein [3,5,13]. In an attempt to avoid vascular injury and limit SD standard deviation blood loss during spine exposure, it is essential to obtain control of the vessels proximally and/or distally at previously nonoperated levels before mobilization of the vasculature and exposure of the target intervertebral level [13].…”
Section: Discussionmentioning
confidence: 52%
“…The formation of adhesions after the primary surgery increases the potential for iatrogenic injury during the revision exposure [12]. If complications related to anterior exposure of the lumbar spine in primary surgeries have been well reported in the literature [1,5,19], only a few studies have reported the technical difficulties and the complications associated with revision surgeries through an anterior approach [2,9,11,[13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations